Individuating multiple (not one) persons reduces implicit racial bias - Qian, Miao; Heyman, Gail D.; Wu, Mingzhan; Fu, Genyue (Frontiers in Psychology, 2022)
Individuation training that helps humans see multiple other-race targets as distinct rather than as interchangeable can reduce children’s implicit racial bias in the form of more negative other-race associations than own-race associations. However, little is known about which aspects of these interventions are critical for their effectiveness. The present research examines whether children need to learn to differentiate among multiple other-race individuals for these interventions to reduce their level of implicit racial bias, or whether differentiating a single other-race individual is sufficient. We addressed this question among 4-to-6-year-old Chinese children (N = 66, 31 girls) who engaged in coordinated movement with Black instructors for 2 min. There were two between-subject conditions: in a differentiation condition, there were four different Black instructors, and children had to learn to tell them apart, and in a no-differentiation condition, there was only one Black instructor. Implicit bias was measured using the IRBT, an implicit association test that was developed based on the IAT but is appropriate for young children. We found a reduction in implicit bias against Black people after this interaction in the differentiation condition, but not in the no-differentiation condition. These findings suggest that learning to differentiate among multiple other-race individuals plays a critical role in reducing children’s implicit racial bias.